15_4_6 - 6. F = (x - z)i + (y - z)j - (x + y)k x 2 + y2 = -...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 6. F = (x - z)i + (y - z)j - (x + y)k x 2 + y2 = - (x + y)z . 2 is a given polygonal path from (0,0,0) to (1,1,1) (but any other piecewise smooth path from the first point to the second would do as well). F dr = x 2 + y2 - (x + y)z 2 (1,1,1) = 1 - 2 = -1. (0,0,0) ...
View Full Document

Ask a homework question - tutors are online